answer this. .......... .
...
Attachments:
![](https://hi-static.z-dn.net/files/dcf/1e9c846d6e22bfbdbbb4b383eed3472f.jpg)
Answers
Answered by
3
Heya !!
( X - 1 ) = 0
X = 1
P (X ) = X⁴ - 3X² + 2X + 5
P(1) = (1)⁴ - 3 × (1)² + 2 × 1 + 5
=> 1 - 3 + 2 + 5
=> 8 - 3
=> 5
On dividing X⁴ - 3X² + 2X + 5 by (X - 1 ) , we get remainder = 5.
( X - 1 ) = 0
X = 1
P (X ) = X⁴ - 3X² + 2X + 5
P(1) = (1)⁴ - 3 × (1)² + 2 × 1 + 5
=> 1 - 3 + 2 + 5
=> 8 - 3
=> 5
On dividing X⁴ - 3X² + 2X + 5 by (X - 1 ) , we get remainder = 5.
Similar questions